DEVELOPMENT OF STAD COOPERATIVE BASED LEARNING SET ASSISTED WITH ANIMATION MEDIA TO ENHANCHE STUDENTS’ LEARNING OUTCOME IN AN ISLAMIC JUNIOR HIGH SCHOOL - Zubaidillah, M. M.; Kirana, K.; Poedjiastoeti, S. (Jurnal Pendidikan IPA Indonesia, 2016)
This study aimed to develop a cooperative learning set (lesson plan, students’ worksheet, and its evaluation) which is assisted with animation media to enhance students’ learning outcome. The development of the learning set used 4D model, which had been tested to 30 students of grade VII at MTs Roudlotun Nasyiin Mojokerto in even semester of academic year 2015/2016. The research was conducted by one group pre-test - post-test design. Then, data was descriptive-qualitatively analyzed. The results of this study is as follow 1) learning set validity is in valid category, 2) practicability of the learning set was shown by accomplishment of the qualified lesson plan and the students’ activities, 3) the effectiveness was judged from the raise of learning outcome. Conclusion of this study is that the cooperative based learning set assisted with animation media is proper and can be used to enhance students’ learning outcome